Neurologic Complications after Particle Embolization of Intracranial Meningiomas - Bendszus, Martin; Monoranu, Camelia Maria; Schütz, Ansgar; Nölte, Ingo; Vince, Giles H.; Solymosi, László (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Preoperative embolization of meningiomas is frequently used to facilitate surgery and to reduce intraoperative blood loss. The purpose of this study was to evaluate the frequency of procedure-related neurologic complications during and after particle embolization of intracranial meningiomas.METHODS: Between 1996 and 2004, 185 consecutive patients underwent particle embolization of an intracranial meningioma. Devascularization was performed by means of superselective probing of the tumor-feeding vessels and ensuing free-flow embolization with spherical particles. All procedures were performed with systemic heparinization.RESULTS: Six patients (3.2%) had ischemic events with neurologic deficit. Two had amaurosis, and four patients presented with hemiparesis. Hemorrhage occurred in six patients (3.2%). In five of these patients, rapid microsurgical tumor removal resulted in a favorable outcome without persistent neurologic deficit. In one patient, massive intratumoral, subarachnoid, and subdural hemorrhage was lethal.CONCLUSION: Particle embolization of meningiomas is associated with a substantial risk of ischemic and hemorrhagic events. The individual risk-to-benefit ratio of embolization should be thoroughly considered.